Vegetation and climate during the penultimate interglacial of the northeastern Russian Arctic: the Lake El'gygytgyn pollen record. (22nd January 2019) - Zhao, Wenwei; Andreev, Andrei A.; Tarasov, Pavel E.; Wennrich, Volker; Melles, Martin
Abstract : We present a high‐resolution reconstruction of the vegetation and climate dynamics during the penultimate interglacial, corresponding with Marine Isotope Stage (MIS) 7, based on detailed palynological analyses of lacustrine sediments from Lake El'gygytgyn, northeastern Siberia. The analysed sediments were deposited between 246 and 181 ka ago (late MIS 8 to early MIS 6.6). The interglacial vegetation was characterized by herb and shrub (mainly alder and birch) dominated plant communities. Pollen‐based biome reconstruction shows a dominance of the tundra (TUND) biome, thus indicating rather open vegetation. Warmer intervals (MIS 7.5, 7.3 and 7.1) were marked by an increase in the cold deciduous forest (CLDE) biome scores and a synchronous decrease in the cold steppe (STEP) biome scores. The thermal maximum occurred during MIS 7.1, as indicated by the highest CLDE biome scores occurring in this period, and lasted 10 ka, possibly favoured by the high precession‐related summer insolation and the legacy of the preceding mild and dry stadial (MIS 7.2). In contrast, MIS 7.3 and 7.5 were characterized by shorter durations ( 4 ka) and lower summer temperatures. The preceding cold glacial and stadial (MIS 8 and 7.4, respectively) might have led to an extensive distribution of permafrost that hindered vegetation development during the subsequent warm intervals. MIS 7.4 and 6.6 were cold and wet, probably triggered by low obliquity values and coevally low precession‐related summer insolation. As a result, these periods were marked by significantly reduced summer temperatures and an enhanced snow‐ice albedo feedback. The obtained reconstructions provide potential scenarios for future climate changes and allow a better understanding of the relationship between vegetation, climate and external/internal forcings in the high latitudes.